Intestinal microbial-derived sphingolipids are inversely associated with childhood food allergy - Lee-Sarwar, Kathleen; Kelly, Rachel S.; Lasky-Su, Jessica; Moody, D. Branch; Mola, Alex R.; Cheng, Tan-Yun; Comstock, Laurie E.; Zeiger, Robert S.; O'Connor, George T.; Sandel, Megan T.; Bacharier, Leonard B.; Beigelman, Avraham; et al. (Journal of allergy and clinical immunology, 2018)
[...]we adjusted for age in all analyses, performed sensitivity analyses of key results adjusting for other potential confounders, and tested for associations between mode of delivery and phenotype-associated microbiome and metabolome perturbations. [...]fecal lipid iNKT-cell activation was significantly lower among subjects born by Cesarean section than among subjects born by vaginal delivery (P = .049). Asthma or recurrent wheeze was based on parental report of physician diagnosis of asthma or recurrent wheeze in the first 3 years of life as previously reported.4 Questionnaire responses were used to determine whether a child was ingesting breast milk and/or formula, and whether solid foods had been introduced at the time of stool sample collection as previously described.E1Fecal sample collection and profiling Stool collection and microbiome profiling methods have been described in detail previously.E2 DNA extraction was performed on the stool samples and sequencing of the bacterial 16S V3 to V5 hypervariable regions was performed by pyrosequencing (Roche 454 Titanium platform) at the Genome Center (TGI) at Washington University in St Louis, Mo. Subject Food Reaction∗ Age (mo) reported Diagnosis method Serum specific IgE (kU/L) Walnut Peanut Egg white Milk Wheat Soybean 1 Sesame seed Unknown 24 Blood and skin test <0.10 1.00 5.42 0.67 0.42 0.63 Egg Unknown 24 Other nut Unknown 24 Peanut Rash 24 2 Soy Diarrhea, nausea, hives 12 Blood and skin test <0.10 2.05 22.4 1.9 0.65 1.27 Wheat Diarrhea, nausea, hives 12 Peanut Diarrhea, nausea, hives 12 Egg Diarrhea, nausea, hives 12 Other nut Unknown 15 Fish Diarrhea, nausea, hives 24 3 Milk Hives, nausea, wheeze, worsened eczema 12 Blood test and skin test 3.05 8.72 5.03 9.88 5.06 3.89 Egg Nausea, vomiting, wheeze, sneezing/runny nose, watery eyes, hives, worsened eczema, fatigue 12 Peanut Nausea 12 Other fish Hives, nausea, diarrhea, worsened eczema, facial swelling, fussiness 12 Soy Hives, fussiness, vaginal itching, nausea, diarrhea 18 Shellfish Facial swelling, hives, worsened eczema, fussiness, nausea, diarrhea 18 Wheat Hives, fussiness, vaginal itching, nausea 21 4 Shellfish Hives, worsened eczema, nausea 12 Blood test and skin test 5.03 1.33 0.53 <0.10 0.38 0.28 Other fish Hives, worsened eczema, nausea 12 Egg Hives, wheeze, worsened eczema, nausea 12 Hot dog Hives 15 Milk Hives, worsened eczema, nausea 24 Wheat Hives 24 Peanut Hives, worsened eczema, nausea 27 5 Egg Nausea, hives, fatigue 18 Skin test 0.66 1.32 1.59 4.24 0.78 2.28 6 Peanut Hives, wheezing, sneezing, red eyes 24 History 12.7 >100 38.5 26 29 96.3 7 Other nut Eyes swelled shut, itchy 36 Skin test 0.72 2.07 4.41 8.51 1.95 0.96 8 Unknown Unknown 15 Blood test 0.25 >100 0.71 <0.10 0.15 2.2 Peanut Hives 24 9 Peanut Hives on 1 body part only 15 Blood and skin test 1.54 9.76 5.67 0.94 2.07 2.96 Egg Nausea, hives 15 Pea Hives on 1 body part only 24 Lentil Hives on 1 body part only 24 Other nut Unknown 30 10 Peanut Not asked† 12 Not asked† <0.10 0.79 0.43 0.25 0.27 <0.10 Egg Not asked† 12 11 Egg Not asked† 12 Not asked† <0.10 <0.10 0.62 <0.10 <0.10 <0.10 12 Egg Hives on 1 body part only, nausea, cough 27 Blood test <0.10 0.37 3.75 1.88 0.90 0.91 Candy/sweets Nausea 36 Table E1 Clinical history and serum specific IgE for food-allergic subjects Characteristic All children (n = 81) All subjects (n = 83) Subjects with iNKT-cell activity data (n = 57) Food allergic (n = 12) Food sensitive (n = 32) Control (n = 37) P value Food allergic (n = 8) Food sensitive (n = 22) Control (n = 27) P value Sex, n (%) .66 .17 Male 41 (51) 5 (42) 18 (56) 18 (49) 2 (25) 14 (64) 13 (48) Female 40 (49) 7 (58) 14 (44) 19 (51) 6 (75) 8 (36) 14 (52) Race/ethnicity, n (%) .94 .98 Black, non-Hispanic 34 (42) 6 (50) 13 (41) 15 (41) 4 (50) 9 (41) 10 (37) White, non-Hispanic 26 (32) 4 (33) 11 (34) 11 (30) 2 (25) 6 (27) 9 (33) Hispanic 21 (26) 2 (17) 8 (25) 11 (30) 2 (25) 7 (32) 8 (30) Birth by Cesarean section, n (%) 24 (30) 6 (50) 5 (16) 13 (35) .052 5 (63) 2 (9) 9 (33) .01 Gestational age (wk), mean ± SD 39.1 ± 1.6 39.4 ± 1.7 38.9 ± 1.9 39.4 ± 1.4 .48 39.3 ± 1.6 38.8 ± 2.2 39.4 ± 1.4 .79 Number of living children born to mother, mean ± SD 0.9 ± 0.9 1.2 ± 0.9 1.0 ± 0.9 0.8 ± 0.9 .40 1.3 ± 0.9 0.8 ± 0.8 0.8 ± 0.9 .36 Antibiotic exposure, n (%) Perinatal antibiotics 35 (43) 8 (67) 11 (34) 16 (43) .16 5 (63) 8 (36) 11 (41) .44 By age 6 mo 15 (19) 2 (17) 5 (16) 8 (22) .86 1 (13) 3 (14) 7 (26) .59 By age 3 y 69 (85) 11 (92) 29 (91) 29 (78) .36 7 (87) 21 (95) 20 (74) .10 Pet dog in home, n (%) In first 6 mo of life 22 (28) 3 (33) 6 (19) 13 (36) .31 2 (25) 3 (14) 10 (37) .19 Between age 6 and 36 mo 32 (41) 3 (33) 13 (43) 16 (43) .52 2 (25) 10 (50) 11 (41) .53 Pet cat in home, n (%) In first 6 mo of life 11 (14) 2 (17) 4 (13) 5 (14) .91 1 (13) 2 (9) 4 (15) .86 Between age 6 and 36 mo 20 (25) 6 (50) 5 (17) 9 (24) .10 3 (38) 2 (10) 6 (22) .22 Daycare by age 3 y, n (%) 43 (53) 7 (58) 15 (47) 21 (57) .72 4 (50) 10 (45) 14 (52) .93 Age at stool sample collection (mo), mean ± SD 4.6 ± 1.1 5.0 ± 1.0 5.0 ± 1.0 4.1 ± 1.0 <.01 5.0 ± 1.0 5.1 ± 1.0 4.2 ± 1.1 .02 Diet at stool sample collection, n (%) Breast-feeding 34 (42) 6 (50) 13 (41) 15 (41) .91 4 (50) 7 (32) 12 (44) .57 Formula 50 (62) 7 (58) 20 (63) 23 (62) 1 4 (50) 16 (73) 17 (63) .51 Solid foods 33 (41) 6 (50) 19 (61) 8 (22) <.01 4 (50) 12 (57) 7 (26) .07 Asthma/recurrent wheeze by age 3 y, n (%) 25 (31) 8 (67) 9 (28) 8 (22) .02 6 (75) 7 (32) 4 (15) <.01 VDAART treatment group, n (%) 1 1 4400 IU/d vitamin D 41 (51) 6 (50) 16 (50) 19 (51) 4 (50) 11 (50) 13 (48) 400 IU/d vitamin D 40 (49) 6 (50) 16 (50) 18 (49) 4 (50) 11 (50) 14 (52) Study center, n (%) .27 .71 Boston 23 (28) 4 (33) 8 (25) 11 (30) 1 (13) 2 (9) 7 (26) St Louis 42 (52) 7 (58) 20 (63) 15 (41) 3 (38) 7 (32) 9 (33) San Diego 16 (20) 1 (8) 4 (13) 11 (30) 4 (50) 13 (59) 11 (41) Maternal education, n (%) .92 .74 Less than high school 10 (12) 1 (8) 3 (9) 6 (16) 0 (0) 3 (14) 4 (15) High school or technical school 26 (32) 5 (42) 11 (34) 10 (27) 4 (50) 8 (36) 6 (22) Some college 10 (12) 2 (17) 4 (13) 4 (11) 1 (13) 3 (14) 3 (11) College graduate or graduate school 35 (43) 4 (33) 14 (44) 17 (46) 3 (38) 8 (36) 14 (52) Household income (US $), n (%) .57 .55 <30,000 29 (36) 6 (50) 12 (38) 11 (30) 5 (63) 8 (36) 8 (30) 30,000-49,999 11 (14) 1 (8) 5 (16) 5 (14) 0 (0) 4 (18) 4 (15) 50,000-74,999 9 (11) 1 (8) 3 (9) 5 (14) 1 (13) 3 (14) 4 (15) 75,000-99,999 8 (10) 1 (8) 1 (3) 6 (16) 1 (13) 0 (0) 4 (15) 100,000-149,999 10 (12) 2 (17) 2 (6) 6 (16) 1 (13) 1 (5) 4 (15) At least 150,000 5 (6) 0 (0) 4 (13) 1 (3) 0 (0) 2 (9) 1 (4) Refused to say or unknown 9 (11) 1 (8) 5 (16) 3 (8) 0 (0) 4 (18) 2 (7) Table E2 Baseline characteristics of children and upstream predictors of the intestinal microenvironment Food-allergic (n = 12) vs control (n = 37, reference) Food-sensitive (n = 32) vs control (n = 37, reference) Food-allergic (n = 12) vs food-sensitive (n = 32, reference) Metabolite Odds ratio (95% CI) P value Metabolite Odds ratio (95% CI) P value Metabolite Odds ratio (95% CI) P value 7-Methylguanine 0.29 (0.11-0.63) .004 3-Ketosphinganine 2.49 (1.37-4.89) .004 3-Hydroxypalmitate 0.23 (0.07-0.59) .01 Docosapentaenoate (n3 DPA; 22:5n3) 0.24 (0.07-0.64) .01 Pimelate (heptanedioate) 2.83 (1.38-6.29) .01 Ribonate 0.32 (0.13-0.69) .01 2-Aminophenol 3.20 (1.40-8.68) .01 Pyridoxine (vitamin B6) 3.08 (1.40-7.63) .01 1-Palmitoyl-GPI (16:0) 0.25 (0.08-0.63) .01 Bilirubin (E,Z or Z,E)∗ 0.20 (0.05-0.62) .01 Cis-urocanate 0.24 (0.07-0.66) .01 1-Palmitoyl-GPS (16:0)∗ 0.25 (0.08-0.65) .01 Histidine 0.11 (0.01-0.53) .01 Diacetylchitobiose 0.38 (0.16, -0.79) .01 I-urobilinogen 0.42 (0.20-0.79) .01 N-formylmethionine 0.28 (0.09-0.72) .01 N-acetylglutamate 0.25 (0.07-0.73) .02 Sphinganine 0.15 (0.03-0.56) .01 I-urobilinogen 0.43 (0.20-0.82) .02 5alpha-pregnan-3beta,20alpha-diol monosulfate (1) 3.04 (1.31-8.77) .02 2-Methylserine 0.32 (0.11-0.75) .02 Dihomo-linolenate (20:3n3 or n6) 0.25 (0.06-0.66) .02 N-carbamoylaspartate 0.38 (0.15-0.81) .02 13-Methylmyristate 0.39 (0.17-0.82) .02 Serine 0.11 (0.01-0.59) .02 N-acetylasparagine 0.26 (0.08-0.78) .02 Dihomo-linolenate (20:3n3 or n6) 0.24 (0.06-0.67) .02 2-Methylserine 0.20 (0.04-0.68) .03 Lysylleucine 2.23 (1.15-4.69) .02 Glycylisoleucine 0.25 (0.07-0.70) .02 5,6-Dihydrothymine 0.40 (0.16-0.86) .03 Vanillic alcohol sulfate 0.42 (0.18-0.86) .03 D-urobilin 0.40 (0.17-0.83) .02 3-Hydroxypalmitate 0.27 (0.07-0.79) .03 Docosahexenoylcarnitine (C22:6)∗ 0.37 (0.14-0.83) .03 Docosapentaenoate (n3 DPA; 22:5n3) 0.26 (0.07-0.74) .02 Phenethylamine 0.32 (0.10-0.83) .03 Ursodeoxycholate sulfate (1) 0.57 (0.34-0.92) .03 7-Methylguanine 0.47 (0.23-0.90) .03 D-urobilin 0.42 (0.18-0.91) .04 3-Methylglutarate/2-methylglutarate 2.35 (1.14-5.35) .03 Sucrose 0.37 (0.14-0.85) .03 Ursodeoxycholate sulfate (1) 0.45 (0.20-0.90) .04 N-palmitoylserine 1.87 (1.08-3.36) .03 1-Palmitoyl-GPE (16:0) 0.20 (0.04-0.73) .03 Tryptamine 0.44 (0.19-0.90) .04 Malonylcarnitine 0.39 (0.16-0.87) .03 21-Hydroxypregnenolone disulfate 0.31 (0.09-0.80) .03 2,3-Dimethylsuccinate 3.06 (1.09-9.72) .04 13-Methylmyristate 1.97 (1.08-3.80) .03 N-acetylglycine 3.33 (1.21-11.18) .03 Oleoyl-linoleoyl-glycerol (18:1/18:2) [1] 2.56 (1.09-6.94) .04 Dopamine 3-O-sulfate 0.45 (0.21-0.90) .03 Alpha-CEHC 0.32 (0.10-0.840) .03 Palmitoyl-linoleoyl-glycerol (16:0/18:2) [1]∗ 2.56 (1.08-7.07) .04 Glutaminylleucine 2.58 (1.12-6.57) .03 Glycerophosphoserine∗ 0.28 (0.08-0.82) .03 Tyrosine 0.16 (0.02-0.86) .04 N2,N6-diacetyllysine 0.41 (0.17-0.90) .03 Bilirubin (E,Z or Z,E)∗ 0.32 (0.10-0.87) .04 Formiminoglutamate 0.36 (0.11-0.90) .04 N-acetyl-aspartyl-glutamate (NAAG) 0.41 (0.17-0.91) .04 Glycylvaline 0.24 (0.05-0.87) .04 Linolenate (alpha or gamma; [18:3n3 or 6]) 0.27 (0.06-0.86) .04 N-alpha-acetylornithine 0.39 (0.15-0.91) .04 Linoleoyl ethanolamide 0.42 (0.17-0.94) .04 Linoleoyl-linolenoyl-glycerol (18:2/18:3) [2]∗ 2.39 (1.04-6.06) .05 Allo-threonine 0.40 (0.15-0.90) .04 3-Ureidoisobutyrate 0.45 (